An Early Roman Hiding Complex at ͑Enot Sho͑im, Central Lower Galilee. (June 2015) - Leibner, Uzi; Shivtiel, Yinon; Distelfeld, Nir
Abstract : Following a report that a tractor disturbed a subterranean hiding complex at ͑Enot Sho͑im, a survey and archaeological excavation were conducted at the site for several days. Study of its abundant datable finds showed that it had probably been sealed since the 2nd or 3rd century CE. This article introduces the site and furnishes new information about subterranean hiding complexes in the Galilee.